Perancangan Database SystemInformasi Pemetaan Trayek Bus Sekolah dan Halte Di Central Business District (CBD) Bangkinang (Studi Kasus Di Dinas Perhubungan Kabupaten Kampar) - Irma Apryliyana; Novi Yona Sidratul Munti; Hanantatur Adeswastoto (Jurnal Inovasi Teknik Informatika, 2021)
Bangkinang City is the capital of Kampar Regency, Riau Province, which is 60 km from Pekanbaru City (the capital of Riau Province). As the district capital close to the provincial capital, Bangkinang is also a liaison with the province of West Sumatra. Bangkinang which is one of the centers of business and commercial activities such as trade, education, transportation, offices/public services, and so on. Along with the development of increasingly advanced technology, the world of work is required to improve work performance. One of the jobs that strongly supports development in Bangkinang is to facilitate students and educators with transportation buses or school buses. These buses are usually used to transport students and educators to and from schools. This bus always operates according to its route. However, the lack of information obtained by the community causes many educators and students not to optimize the facilities provided by the Kampar Regency Transportation Service. The system designed is a web-based system as a medium to provide information to the public. The programming languages used are HTML, PHP, and Mysql as databases which are expected to make it easier for admins to manage data efficiently. To support this, we need a geographic information system that is used by students and the public to obtain information on school bus routes and bus stops.